Dispersion properties of artificial topological insulators based on an infinite double-periodic array of elliptical quartz elements - Ivzhenko, L. I.; Polevoy, S. Yu.; Odarenko, E. N.; Tarapov, S. I. (ІРЕ НАН України, 2021)
Subject and Purpose. Special features of all-dielectric electromagnetic analogues of topological insulators in the microwave range are considered, aiming at studying the influence of geometrical and constitutive parameters of topological insulator elements on the dispersion properties of topological insulators based on a two-dimensional double-periodic array of dielectric elements. Methods and Methodology. Th e evaluation of dispersion properties and electromagnetic field spatial distribution patterns for topological insulators is performed using numerical simulation programs. Results. The electromagnetic analogue of a topological insulator based on a double-periodic array of elliptical quartz cylinders has been considered. By numerical simulation, it has been demonstrated that the electromagnetic properties of the structure are control-lable by changing the quartz uniaxial anisotropy direction without any changes in other parameters. A combined topological insulator made up of two adjoining ones differing in shapes of their unit cells has been considered with the numerical demonstration that frequencies of surface states are controllable by choosing the quartz uniaxial anisotropy direction. It has been shown that it is at the interface of two different in shape unit cells that the electromagnetic field concentration at a surfacestate frequency takes place. Conclusion. A possibility has been demonstrated of controlling microwave electromagnetic properties of topological insulators by changing their geometric parameters and permittivity of the constituents. From a practical point of view, topological insulators can be used as components of microwave transmission lines and devices featuring very small propagation loss.
Keywords: topological insulator; uniaxial anisotropy; microwave range; photonic crystal